2007
DOI: 10.1016/j.mcm.2006.04.009
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of higher order fluxes in non-equilibrium thermodynamics

Abstract: The connection between the balance structure of the evolution equations of higher order fluxes and different forms of the entropy current is investigated on the example of rigid heat conductors. Compatibility conditions of the theories are given. Thermodynamic closure relations are derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…be found for instance in [18]. An alternative way, leading to a gradient dependent free energy density, can be found in [46][47][48], where in the exploitation of the dissipation inequality not only the evolution equations are taken into account, but also the gradients of evolution equations.…”
Section: Discussionmentioning
confidence: 99%
“…be found for instance in [18]. An alternative way, leading to a gradient dependent free energy density, can be found in [46][47][48], where in the exploitation of the dissipation inequality not only the evolution equations are taken into account, but also the gradients of evolution equations.…”
Section: Discussionmentioning
confidence: 99%
“…The flux of the heat flux is a second-order tensor usually considered in non-local models of heat transport [24,[50][51][52][53]. We aim to obtain evolution equations for q and Q compatible with the second law of thermodynamics, which requires a positive definite character of the entropy production.…”
Section: Approximate Constitutive Equation For Heat Flux In Gradmentioning
confidence: 99%
“…So, the definition of the macroscopic material velocity of the component A, v A (x, t), i.e., the mean velocity of the component A of the mixture, is 17) and equation (5.7) leads to the macroscopic mass balance of component A (4.4) if we take…”
Section: Mesoscopic Balance Equations For the Components Of The Mixturementioning
confidence: 99%
“…This differential equation is derived either from an Irreversible Thermodynamics treatment [6,7] of the dissipation inequality (for other applications see [8,9,10,11,12,13]), or a balance type equation for the non-convective fluxes, here the diffusion flux, is postulated in Rational Extended Thermodynamics [14,5,15]. For a purely macroscopic derivation of balance type differential equations for higher order fluxes see [16,17]. Within Rational Extended Thermodynamics it has been shown that the resulting system of field equations is symmetric hyperbolic with a convex extension [18,5,19], thereby allowing for finite speeds of disturbances only [20,21,18].…”
Section: Introductionmentioning
confidence: 99%